Verslo organizacijos informacinės aplinkos tyrimas - Matkevičienė, Renata (Information & Media, 2007)
Šiandienė visuomenė ir rinka iš organizacijų reikalauja ne tik kokybiškų produktų ir paslaugų, tačiau ir gebėjimo suvokti besikeičiančius poreikius, kintančius, gal tiksliau – didėjančius gyvenimo kokybės reikalavimus. Organizacijoms išlikti konkurencingoms padeda efektyvus aplinkos stebėjimas, vertinimas ir gebėjimas prisitaikyti prie jos kismo. Šio straipsnio tikslas – išanalizuoti organizacijos aplinkos veiksnius, turinčius įtakos organizacijos veiklos efektyvumui ir nurodančius organizacijos veiksmus informacinei organizacijos aplinkai tirti. Straipsnyje organizacija analizuojama kaip atvira sistema, remiantis sistemų teorija pristatoma organizacijos sąveika su išorės aplinka, aptariami esminiai išorės aplinkos veiksniai, lemiantys verslo organizacijos veiklą. Analizuojant ir vertinant verslo organizacijos išorės aplinką supažindinama su užsienio autorių darbais, pateikiami Lietuvos verslo organizacijų atliktos apklausos rezultatai. Investigation of business enterprise information environment Renata Matkevičienė Summary Contemporary society and market request from modern organizations qualitative products and services, as well it demands for skills to understand demands and requirements that are changing rapidly. All these conditions call for claims for life quality. Organizations should make effective environmental scanning and evaluation of it, as well they should have an ability to adjust to changes in it. The aim of the article is to analyze factors of environment that have impact on effectiveness of organization activities and setting the set of organizational actions that are used in informational environmental scanning. In the article there are presented several main aspects of the analyzed item: organization as an open system, interaction of organization with external environment, main factors of external environment, that impact organizational activities. There are discussed works of Lithuanian and foreign authors on business organization external environment scanning, as well there are presented results of Lithuanian business enterprises survey. Talking about modern organization there should be taken to account several important aspects of discussion: first of all there should be mentioned that contemporary organization is acting in social environment that is impact by humans, as well as by external social forces; second, contemporary organizations could be analyzed in different aspects based on definition of organization. Some organizations could be defined as an effective mechanism with bureaucratic governance, with clear role of managerial personnel and even more clear understanding or importance and set of organizational structure. Wideness of definition of contemporary organization implies understanding of business enterprise as complex, miscellaneous and open system. Based on the results of survey presented in the article there are made supposition that set of metaphors for organization depends on executives of organization, and partly on market place and character of organizational activities. Definition of modern organization implies duality of organizational activities: 1) organizational orientation toward external activities (possibilities and skills to evaluate possible influence of external factors to organizational activities and to plan possible reaction to external conditions), and 2) organizational orientation toward internal factors and activities (possibilities and skills of modern organization to overhaul internal activities and possibilities to react and to adapt to changes in environment). Understanding of business organization as an open system allows and indicates organizational orientation not only toward aims, tasks, activities, but organizational behavior in external environment too. External environment of business enterprise is quite complicate: it involves clients, customers, competitors, suppliers, professional unions, public and governmental institutions. As well those groups of external environment could be formed in 1) contextual or target groups, and 2) general audience. Modern organization and its activities mainly depend on informational and communication skills that warrant possibilities of external environment scanning. Informational environment scanning is critical for modern organization because it provides information on organizational positions, clients, their needs, general competitive environment. External environment scanning in business enterprise provides information from various sectors and ensures organizational learning possibilities that are substantial for modern knowledge seeking organization: for long term planning, for decision making and for setting organizational development and growth.